PENANGGULANGAN KEJAHATAN INSIDER TRADING DI DALAM PASAR MODAL - M Zen Abdullah (Jurnal LEX SPECIALIS, 2010)
To increased economic roll in private aspect more fund is needed to realized, and the one legal institution to rule that is a stock market, in modern nation stock market is have a vital posisition to the economic policy of a whole nation, in this case stock market must be clean from a dirty practically like insider trading, as one of a crime in stock market insider trading have a vital posostion to to ensure the goodwill of a stock market because trust from the investor is really needed to ensure the stock market will live on, this is the reason why insider trading must be forbided in stock market, this journal will explained about the prevention of insider trading as a crime in stock market. Key Note: Insider trading as a crime in stock market